Ocean travel and cruising : a cultural analysis - Berger, Arthur Asa, 1933- (Haworth Hospitality Press, 2004)
A one-of-a-kind analysis of ocean cruising! In Ocean Travel and Cruising: A Cultural Analysis, noted author Arthur Asa Berger turns his critical eye to the phenomenon of ocean cruising. This academically solid yet reader-friendly book brings a multidisciplinary cultural studies approach to the subject, examining ocean cruising from economic, semiotic, sociological, psychoanalytic, and marketing perspectives, and offering insights not provided by the more traditional sociological approaches to the subject. You'll explore cruise demographics, the relationship between cruising and gender.